Teoria do comportamento planejado e teoria dos valores humanos: a influência na intenção empreendedora de estudantes universitários na região Sudoeste do Paraná - Marcon, Déborah Luiza (2018)
Entrepreneurs stand out as agents for strengthening local economies, as a result of their power to promote economic growth linked to their businesses. Investigating the formation of Entrepreneurial Intent (EI) is determinant for the understanding of the whole process of entrepreneurship. Based on Schwartz’s Theory of Human Values (THV) (2001) and Ajzen’s Theory of Planned Behavior (TPB), the present study aimed to identify the influence of human values and the planned behavior in EI of university students of 11 educational institutions, established in the southwestern region of Paraná, in the south of Brazil. The research universe covered the 3rd and 4th year students of the classroom-based administration courses. The instrument of data collection was a questionnaire, composed by the following items: (1) sociodemographic questionnaire, (2) Schwartz’s Portrait Values Questionnaire (PVQ) (2001), (3) Liñán and Chen’s Entrepreneurial Intention Questionnaire (2009) and (4) three items of Thompson’s Entrepreneurial Intention Scale (2009). Through the Multiple Linear Regression analysis, the results showed that the Personal Attitudes construct was shown to be the most influential in EI, in relation to the other constructs. The construct Perception of Behavior Control, in order of greater influence, ranked second. For the human values constructs, only the values of self-promotion were significant, having a positive influence on the EI of the students surveyed. The TCP-based model allowed to explain 51.1% of the variance of the EI, which is an average value compared to the values found in previous investigations, ranging from 20% to 65%. The human values model added to TCP allowed to explain 51.8% of the variance in EI. The present research evidenced the regionality factor, making possible future comparative studies between Brazilian states and regions.